2020
DOI: 10.12659/msm.926789
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Improves Lipid Metabolism Through Changes in Gut Microbiota in Diet-Induced Obese Mice

Abstract: Background The mechanism of how intermittent fasting (IF) improves metabolism is not fully understood. Our study aimed to explore the effect of IF on lipid metabolism in obese mice, specifically on the intestinal flora. Material/Methods Diet-induced obese (DIO) mice were subjected to ad libitum (AL) feeding or IF (alternate-day fasting) for 30 days. We examined the lipid metabolism, fat distribution, gene expression of lipid metabolism, and intestinal flora in the mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Three studies have been conducted on diet-induced obese mouse model. Dengy Y, et al indicated that 24-h fasting for 30 days increased the bacterial diversity in the intestinal flora, enriched the relative abundance of Allobaculum , and decreased the ratio of Firmicutes to Bacteroidetes which led to lowering fat accumulation and increasing white fat conversion to beige [ 28 ]. In contrast, Li G, et al showed that every other day fasting regimen in diet-induced obese mouse increased the operational taxonomic unit abundance of Firmicutes, but decreased the most other phyla including Bacteriodetes and Actinobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies have been conducted on diet-induced obese mouse model. Dengy Y, et al indicated that 24-h fasting for 30 days increased the bacterial diversity in the intestinal flora, enriched the relative abundance of Allobaculum , and decreased the ratio of Firmicutes to Bacteroidetes which led to lowering fat accumulation and increasing white fat conversion to beige [ 28 ]. In contrast, Li G, et al showed that every other day fasting regimen in diet-induced obese mouse increased the operational taxonomic unit abundance of Firmicutes, but decreased the most other phyla including Bacteriodetes and Actinobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some studies have shown that IF cause weight loss, reduce lipid peroxidation, and hepatic steatosis on obese mice through changes in microbial profile. Also, it has been reported in this study that IF led to a significant increase in the intestinal flora community diversity [Firmicutes to Bacteroidetes (F/B ratio) and relative increase in the Allobaculum abundance] ( 23 ). Increasing the abundance of Firmicutes following fasting diets can increase the production of short-chain fatty acids (SCFAs).…”
Section: Experimental Studiesmentioning
confidence: 57%
“…ADF diet also led to enhanced energy expenditure by promoting beige adipogenesis, and ameliorated weight gain and other metabolic disorders 118 . In another study, Lactobacillus levels were reproducibly elevated upon ADF only in mice fed with normal chow, whereas the genus Allobaculum was identified as exclusively enriched in mice undergoing ADF and fed with high‐fat diets 121 . Interestingly, the Allobaculum genus is an active glucose metabolizer that produces butyrate and lactate 121,122 .…”
Section: Intermittent Fasting and Microbial Regulation In Cardiometab...mentioning
confidence: 98%